Internet connectivity disruption in Colombia (Colombia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Colombia. Data sourced from IODA.
Network Disruption Incident ID: CO-2026-0033. Severity: critical. Confidence: 65%